In vivo determination of the diclofenac skin reservoir: comparison between passive, occlusive, and iontophoretic application - Clijsen R; Baeyens JP; Barel AO; Clarys P (Dove Medical Press, 2015)
Ron Clijsen,1,2 Jean Pierre Baeyens,2 André Odilon Barel,2 Peter Clarys2 1Department of Health Sciences, University of Applied Sciences and Arts of Southern Switzerland, Landquart, Switzerland; 2Faculty of Physical Education and Physiotherapy, Vrije Universiteit Brussel, Brussels, Belgium Aim: There is scarce information concerning the pharmacodynamic behavior of topical substances used in the physiotherapy setting. The aim of the present study was to estimate the formation and emptying of the diclofenac (DF) skin reservoir after passive, semiocclusive, and electrically assisted applications of DF.Subjects and methods: Five different groups of healthy volunteers (ntotal=60, 23 male and 37 female), participated in this study. A 1% DF (Voltaren Emulgel) formulation (12 mg) was applied on the volar forearms on randomized defined circular skin areas of 7 cm2. DF was applied for 20 minutes under three different conditions at the same time. The presence of DF in the skin results in a reduction of the methyl nicotinate (MN) response. To estimate the bioavailability of DF in the skin, MN responses at different times following initial DF application (1.5, 6, 24, 32, 48, 72, 96, and 120 hours) were analyzed.Results: At 1.5 hours after the initial DF application, a significant decrease in MN response was detected for the occluded and iontophoretic delivery. Passive application resulted in a decrease of the MN response from 6 hours post-DF application. The inhibition remained up to 32 hours post-DF application for the iontophoretic delivery, 48 hours for the occluded application, and 72 hours for the passive delivery. At 96 and 120 hours post-DF application none of the MN responses was inhibited.Conclusion: The formation and emptying of a DF skin reservoir was found to be dependent on the DF-application mode. Penetration-enhanced delivery resulted in a faster emptying of the reservoir. Keywords: transdermal drug delivery, passive diffusion, occlusion, iontophoresis, diclofenac